The Effect of Profitability, Leverage and Company Size on Tax Avoidance in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange for the 2016-2019 Period - Jesslyn Thesia (Outline Publisher, 2022)
The purpose of this study is to determine the effect of Profitability, Leverage and Size Against Tax Avoidance in food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange. The research methodology used is quantitative method and source data is secondary data. The unit of analysis and observation in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange, with the total population as many as 23 companies. From the population, chosen with purposive sampling method and obtained as many as 14 companies for 4 periods, namely the period 2016-2019 which amounted 56 samples. T test results show that the Profitability has no significant effect on Tax Avoidance in food and beverage sub-sector manufacturing companies, Leverage has no significant effect on Tax Avoidance in food and beverage sub-sector manufacturing companies and Size has a significant effect on Tax Avoidance in food and beverage sub-sector manufacturing companies. F test results indicate that the variable Profitability, Leverage and Size significantly influence Tax Avoidance in food and beverage sub-sector manufacturing companies. The coefficient of determination test results (Adjusted R2) shows that the Tax Avoidance variable can be explained by the variables of Profitability, Leverage and Size and the remaining Tax Avoidance variable is explained by other variables not included in the research model such as Sales Growth, Audit Comittee and Executive Character.